Peri-implantitis increases the risk of medication-related osteonecrosis of the jaws associated with osseointegrated implants in rats treated with zoledronate - Quintão Manhanini Souza, Eduardo [UNESP]; Felipe Toro, Luan [UNESP]; Franzão Ganzaroli, Vinícius [UNESP]; de Oliveira Alvarenga Freire, Jéssica [UNESP]; Matsumoto, Mariza Akemi [UNESP]; Casatti, Cláudio Aparecido [UNESP]; Tavares Ângelo Cintra, Luciano [UNESP]; Leone Buchaim, Rogério; Mardegan Issa, João Paulo; Gouveia Garcia, Valdir; Theodoro, Leticia Helena [UNESP]; Ervolino, Edilson [UNESP] (Springer Nature, 2024)
This study evaluated the peri-implant tissues under normal conditions and under the influence of experimental peri-implantitis (EPI) in osseointegrated implants installed in the maxillae of rats treated with oncologic dosage of zoledronate. Twenty-eight senescent female rats underwent the extraction of the upper incisor and placement of a titanium dental implant (DI). After eight weeks was installated a transmucosal healing screw on DI. After nine weeks, the following groups were formed: VEH, ZOL, VEH-EPI and ZOL-EPI. From the 9th until the 19th, VEH and VEH-EPI groups received vehicle and ZOL and ZOL-EPI groups received zoledronate. At the 14th week, a cotton ligature was installed around the DI in VEH-EPI and ZOL-EPI groups to induce the EPI. At the 19th week, euthanasia was performed, and the maxillae were processed so that at the implanted sites were analyzed: histological aspects and the percentage of total bone tissue (PTBT) and non-vital bone tissue (PNVBT), along with TNFα, IL-1β, VEGF, OCN and TRAP immunolabeling. ZOL group presented mild persistent peri-implant inflammation, higher PNVBT and TNFα and IL-1β immunolabeling, but lower for VEGF, OCN and TRAP in comparison with VEH group. ZOL-EPI group exhibited exuberant peri-implant inflammation, higher PNVBT and TNFα and IL-1β immunolabeling when compared with ZOL and VEH-EPI groups. Zoledronate disrupted peri-implant environment, causing mild persistent inflammation and increasing the quantity of non-vital bone tissue. Besides, associated with the EPI there were an exacerbated inflammation and even greater increase in the quantity of non-vital bone around the DI, which makes this condition a risk factor for medication-related osteonecrosis of the jaws.